THE ROLE OF CORPORATE CONTROL IN SHAPING SEO EXPENSES - Al-Farsi , Ahmed Khalid; Lopez, Sara Maria (Ayden International Journal of Applied Economics, Finance and Accounting, 2025)
Companies face significant stock price drops, typically ranging from two to three percent, upon announcing seasoned equity offerings (SEOs), as evidenced in various studies (Asquith & Mullins, 1986; Masulis, 1986; Smith, 1986; Jung, Kim, & Stulz, 1996). Smith (1986) further reveals that the market's reaction to equity issuance on the announcement day is approximately 2.88 percent more negative compared to debt issuance. Bayless (1994) supports these findings, suggesting that the issue costs for equity can be 35.4 to 48.6 percent higher than similar debt issues, using the Asquith-Mullin (1986) measure. Lee, Lochhead, Ritter, and Zhao (1996) reinforce the notion of equity financing's elevated costs by reporting that the total direct costs of SEOs average 7.11 percent of total proceeds, while debt issues only represent 2.24 percent. These empirical results collectively highlight that, in general, equity financing is both costly and more expensive than debt financing, making debt a seemingly more attractive option. Nonetheless, individual firms may opt for equity issuances due to other motivating factors